DIPLOMASI BUDAYA KOREA SELATAN DI INDONESIA MELALUI VARIETY SHOW 2 DAYS 1 NIGHT 2020-2021 - Putri Elsa Debora S (2023)
The increasing consumption of Hallyu entertainment products, such as television programs, served as a solution to the limitations of South Korean cultural diplomacy activities in Indonesia during the Covid-19 pandemic, especially in the years 2020-2021. One of the significant efforts in promoting culture indirectly was through the variety show "2 Days 1 Night." This research aims to understand how South Korean cultural diplomacy was conducted indirectly in Indonesia through the "2 Days 1 Night" variety show during the Covid-19 pandemic, particularly in the years 2020-2021. The study utilized the concepts of cultural diplomacy and international broadcasting to analyze the process of cultural diplomacy activities through television broadcasting. The research focused on "2 Days 1 Night" as the subject of investigation and employed a qualitative descriptive method to analyze several broadcasts of the show. Data collection was conducted through 100 respondents. The results of this research revealed that the role of the variety show "2 Days 1 Night" as a medium for conveying South Korean cultural information to the Indonesian society was successful. This was evident through the portrayal of cultural values, such as tourism, cuisine, festivals, language, and others, which managed to pique the interest of the Indonesian audience and foster positive views about South Korea, especially during the years 2020-2021.